Chromatin Remodeling Protein ZmCHB101 Regulates Nitrate-Responsive Gene Expression in Maize - Meng, Xinchao; Yu, Xiaoming; Wu, Yifan; Kim, Dae Heon; Nan, Nan; Cong, Weixuan; Wang, Shucai; Liu, Bao; Xu, Zheng-Yi (Frontiers in Plant Science, 2020)
Nitrate is the main source of nitrogen for plants and an essential component of fertilizers. Rapid transcriptional activation of genes encoding the high-affinity nitrate transport system (HATS) is an important strategy that plants use to cope with nitrogen deficiency. However, the specific transcriptional machineries involved in this process and the detailed transcriptional regulatory mechanism of the core HATS remain poorly understood. ZmCHB101 is the core subunit of the SWI/SNF-type ATP-dependent chromatin remodeling complex in maize. RNA-interference transgenic plants (ZmCHB101-RNAi) display abaxially curling leaves and impaired tassel and cob development. Here, we demonstrate that ZmCHB101 plays a pivotal regulatory role in nitrate-responsive gene expression. ZmCHB101-RNAi lines showed accelerated root growth and increased biomass under low nitrate conditions. An RNA sequencing analysis revealed that ZmCHB101 regulates the expression of genes involved in nitrate transport, including ZmNRT2.1 and ZmNRT2.2. The NIN-like protein (NLP) of maize, ZmNLP3.1, recognized the consensus nitrate-responsive cis-elements (NREs) in the promoter regions of ZmNRT2.1 and ZmNRT2.2, and activated the transcription of these genes in response to nitrate. Intriguingly, well-positioned nucleosomes were detected at NREs in the ZmNRT2.1 and ZmNRT2.2 gene promoters, and nucleosome densities were lower in ZmCHB101-RNAi lines than in wild-type plants, both in the absence and presence of nitrate. The ZmCHB101 protein bound to NREs and was involved in the maintenance of nucleosome occupancies at these sites, which may impact the binding of ZmNLP3.1 to NREs in the absence of nitrate. However, in the presence of nitrate, the binding affinity of ZmCHB101 for NREs decreased dramatically, leading to reduced nucleosome density at NREs and consequently increased ZmNLP3.1 binding. Our results provide novel insights into the role of chromatin remodeling proteins in the regulation of nitrate-responsive gene expression in plants.